TI_GERICHTE 35.2022.61 vom 28. Oktober 2022 , Perizia psichiatrica ex art. 44 LPGA. Rinvio per complemento peritale - TI Tribunale d'appello (2022)
Perizia psichiatrica ex art. 44 LPGA. Rinvio per complemento peritale